Model Energi Pembangkit Listrik Tenaga Surya di Pulau Giliyang Madura - Nurhadi Nurhadi; Mochammad Ali M; Daif Rahuna; Sutopo P Fitri (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2017)
Giliiyang Island is a famous island that has the highest oxygen content in the world, and very beautiful sea, but the location is far from PLN / elctictric grid system. It is necessary to develop environmentally friendly alternative energy. One of alternative energy offered is solar energy. Solar energy is energy that’s form of light and heat from the sun. This energy can be utilized using a range of technologies such as solar heating, solar photovoltaic, solar thermal power, solar architecture, and artificial photosynthesis. Based on the calculation is known that the electrical energy demand for Giliiyang Island is around 1984 kWh. The design of two off-grid solar power systems which each capacity about 1 MWp will require 3000 m2 of land with 780 solar panels that have an intensity of 800 W / m2. Deep cycle battery with 24 V DC 200 AH as storage media required about 504 pieces.